(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
Gastrointestinal (GI) parasitism is one of the major constraints to profitable cattle production in tropical and subtropical regions. This study was conducted in Bhaluka Upazila, with an aim to assess the prevalence and risk factors associated with gastrointestinal parasitism in cattle. A total of 110 fecal samples was collected randomly from cattle and examined using simple sedimentation techniques under the microscope. The results revealed 104 samples were positive which indicated an overall prevalence of 94.54%. Three protozoan species, namely, Balantidium spp., Eimeria spp., and Giardia spp. were detected among the study samples with a prevalence rate of 15.45%, 23.64%, and 1.81%, respectively. Moreover, Paramphistomum spp. (39.09%) was more prevalent than other helminths such as Fasciola spp. (25.45%), Trichuris spp. (10.00%), Dictyocaulus spp. (1.81%) and Strongyloides spp. (1.81%). Moreover, the highest prevalence was observed in trematodes (64.55%), followed by protozoa (40.91%), nematodes (14.55%), and cestodes (2.73%) respectively. Among the samples, a higher prevalence was observed among the calves (100.00%), as opposed to young individuals (93.75%) and adults (18.18%) in the study population. Parasitic infection was more prevalent in the indigenous breed than crossbreed. In addition to this, the infection rate in females was higher (70.90%) than in males (92.31%). The findings provide an epidemiological forecast on the prevalence of gastrointestinal parasitism in cattle, aiding clinicians in diagnosing and preventing GI parasites in cattle. Res. Agric. Livest. Fish. Vol. 12, No. 1, April 2025: 25-33